Cedar Bark Harvest - G.F. MacDonald Collection (1972)
Chief and elder, Elsie Morrison, collecting and preparing cedar bark. These scenes of resource gathering were initiated in order to record some of the traditional practices of the Gitxsan people and to fill some of the gaps left by earlier anthropologist and cultural observers. The objective was to create colour images of practices that were partially captured in earlier black and white photographs and in early texts such as those written by Marius Barbeau and William Beynon. The Book Builders of 'Ksan produced a volume on food collecting and processing practices titled Gathering what the Great Nature provided: food traditions of the Gitksan, by the people of 'Ksan.